Beneficial effects of bile acid receptor agonists in pulmonary disease models. (2nd November 2017) - Comeglio, Paolo; Morelli, Annamaria; Adorini, Luciano; Maggi, Mario; Vignozzi, Linda
ABSTRACT: Introduction : Bile acids act as steroid hormones, controlling lipid, glucose and energy metabolism, as well as inflammation and fibrosis. Their actions are implemented through activation of nuclear (FXR, VDR, PXR) and membrane G protein-coupled (TGR5, S1PR2) receptors. Areas covered : This review discusses the potential of FXR and TGR5 as therapeutic targets in the treatment of pulmonary disorders linked to metabolism and/or inflammation. Obeticholic acid (OCA) is the most clinically advanced bile acid-derived agonist for FXR-mediated anti-inflammatory and anti-fibrotic effects. It therefore represents an attractive pharmacological approach for the treatment of lung conditions characterized by vascular and endothelial dysfunctions. Expert opinion : Inflammation, vascular remodeling and fibrotic processes characterize the progression of pulmonary arterial hypertension (PAH) and idiopathic pulmonary fibrosis (IPF). These processes are only partially targeted by the available therapeutic options and still represent a relevant medical need. The results hereby summarized demonstrate OCA efficacy in preventing experimental lung disorders, i.e. monocrotaline-induced PAH and bleomycin-induced fibrosis, by abating proinflammatory and vascular remodeling progression. TGR5 is also expressed in the lung, and targeting the TGR5 pathway, using the TGR5 agonist INT-777 or the dual FXR/TGR5 agonist INT-767, could also contribute to the treatment of pulmonary disorders mediated by inflammation and fibrosis.